Bridging equity and resilience: A Systematic review of social sustainability in climate change mitigation and adaptation - Yasmin Hageer (12307178) (2025)
Achieving meaningful climate action requires more than technological innovation; it demands social sustainability, equity, and inclusion. This systematic review synthesises findings from 67 peer-reviewed studies (2015–2025), a period marked by the Paris Agreement and Sustainable Development Goals, when social dimensions became central to climate governance. The analysis explores four interconnected themes: climate justice and equity, social resilience, community-driven solutions, and technological strategies for inclusive climate action. Sub-themes were developed inductively through pattern-based analysis, ensuring they emerged from the data rather than being predetermined. Findings show that effective climate outcomes arise when local knowledge, inclusive governance, and marginalised voices are central to decision-making. Persistent challenges include institutional barriers, data inequities, and the exclusion of Indigenous and local knowledge systems. In response, this paper introduces a novel framework that integrates environmental sustainability, digital ethics, and inclusive governance. Unlike techno-centric models, this framework places justice, equity, and community participation at the core of climate strategies. It highlights how participatory AI, GeoAI, big data, and remote sensing can support—rather than replace, local solutions when guided by ethical design and co-creation. By linking emerging technologies with grassroots innovation and traditional stewardship, the framework enables holistic, socially legitimate climate action. Policy recommendations are derived directly from the framework, ensuring alignment between theory, evidence, and practice. These include institutional reforms, equitable financing, capacity-building, and ethically governed digital tools. Ultimately, the study calls for a paradigm shift, from top-down interventions to inclusive, community-led governance that upholds human dignity and leaves no one behind. Other Information Published in: Environmental Science & Policy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.envsci.2025.104243